1987
DOI: 10.1007/bf01116510
|View full text |Cite
|
Sign up to set email alerts
|

Clenbuterol, a beta agonist, induces growth in innervated and denervated rat soleus muscle via apparently different mechanisms

Abstract: Dietary administration of the anabolic agent, clenbuterol, has already been shown to inhibit or reverse denervation-induced atrophy in rat soleus muscles. We now show that the ameliorative effects of clenbuterol in denervated rat muscles are due principally to a large increase in protein synthesis. This results from both an increase in protein synthetic capacity and a normalised translational efficiency. The responses of innervated and denervated muscles are therefore fundamentally different, the changes in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…Interestingly, the protein anabolic dynamic signature for clenbuterol treatment was not in all respects reciprocal to the signature for denervation. Clenbuterol produced a strong response of increased FSRs for cytosolic and structural proteins, as expected (20,57), but its effects on mitochondrial proteins were limited to only the denervated limb, suggesting differential mechanisms and a stronger anabolic response under conditions of muscle atrophy. In addition, consistent with previous reports that denervation induces CA-3 in rat skeletal muscle (62,63), we also observed that denervation increased CA-3 synthesis, whereas most cytosolic protein FSRs were reduced.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the protein anabolic dynamic signature for clenbuterol treatment was not in all respects reciprocal to the signature for denervation. Clenbuterol produced a strong response of increased FSRs for cytosolic and structural proteins, as expected (20,57), but its effects on mitochondrial proteins were limited to only the denervated limb, suggesting differential mechanisms and a stronger anabolic response under conditions of muscle atrophy. In addition, consistent with previous reports that denervation induces CA-3 in rat skeletal muscle (62,63), we also observed that denervation increased CA-3 synthesis, whereas most cytosolic protein FSRs were reduced.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have documented a reduction in mixed muscle protein synthesis rates and content in skeletal muscle tissue (20,57) or in mixed myofibril protein subfractions (37), after denervation, using radioactive amino acid tracers. More recent proteomic approaches have quantified changes in the abundances of specific proteins (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…As soleus muscle is an oxidative muscle, it could be postulated that salbutamol has a specific effect in terms of hypertrophy, namely, it stops the process of muscle fiber atrophy during the denervation period. These changes occurring in denervated muscle fibers under the influence of salbutamol led Maltin et al (18) to think of a classic response of cells to growth factors, with salbutamol acting as an anabolic drug as well as a ß-agonist agent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential therapeutic role for clenbuterol in muscular dystrophy has received much attention (Maltin et al 1987(Maltin et al , 1993Martineau et al 1992;Zeman et al 1994;Hayes & Williams 1994;Dupont-Versteegden et al 1995), the majority of these studies have investigated only whether clenbuterol alters the mass and isometric force-producing capacity of isolated muscles. Whether clenbuterol affects the dynamic properties of dystrophic skeletal muscle has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic treatment with clenbuterol, a âµ-adrenoceptor agonist, has been proposed as a treatment to reverse the muscle atrophy observed with ageing (Carter et al 1991), denervation (Maltin et al 1987(Maltin et al , 1993Zeman et al 1987;Agbenyega & Wareham, 1990), muscle unloading (Delday & Maltin, 1997) and muscle wasting diseases, such as muscular dystrophy (Maltin et al 1987(Maltin et al , 1993Martineau et al 1992;Zeman et al 1994;Dupont-Versteegden, 1996). It is well established that clenbuterol treatment increases muscle mass in a number of different species (Kim & Sainz, 1992) with an increased protein synthesis andÏor decreased protein degradation proposed as the mechanism for the hypertrophy of skeletal muscle (Choo et al 1992;Moore et al 1994).…”
mentioning
confidence: 99%